Fiscal policy and private consumption: Saving decisions: European evidence - Anne Brunila (Bank of Finland, 1997)
This study considers the effects of fiscal policy on private consumption in a framework that encompasses both the conventional (Keynesian) view of fiscal policy and the Ricardian debt neutrality hypothesis.The model is built on Blanchard's stochastic model of intertemporal optimization with finitely lived consumers.As an extension to the basic framework, public consumption is explicitly incorporated in the model.The model also nests the excess sensitivity hypothesis enabling an investigation of the role of current income in consumption.The empirical analysis is based on annual data from ten EU countries covering the years 1961-1994 and uses the nonlinear instrumental variable GMM estimator both in countryspecific and panel estimations.The tests clearly reject Ricardian debt neutrality for the majority of countries in the sample.The deviations from Ricardian neutrality seem to arise from excess sensitivity of consumption to current income rather than from a finite planning horizon on the part of consumers.The results also suggest that in consumers' utility functions, government consumption and private consumption tend to be unrelated or complements rather than substitutes.
URN:NBN:fi:bof-201408071695
Keywords: 330; private consumption; private saving; current income; fiscal policy; planning horizon